Combination of quadrupole isotope dilution mass spectrometry with simultaneous derivatization and spray assisted droplet formation-liquid phase microextraction for the determination of methamphetamine in human urine and serum samples by gas chromatography mass spectrometry - Oflu, Sude; Erarpat, Sezin; Zaman, Buse Tugba; Gunkara, Omer Tahir; Bakirdere, Sezgin; Turak, Fatma (ELSEVIER SCIENCE INC, 2023)
In this study, an analytical method with high accuracy and precision was developed for the determination of methamphetamine in human urine and serum samples by gas chromatography-mass spectrometry (GC-MS). A simultaneous derivatization and spray assisted droplet formation-liquid phase microextraction (SADF-LPME) method was proposed to derivatize and preconcentrate target analyte. Quadruple isotope dilution (ID4) was used to provide high accuracy and precision for methamphetamine determination in the samples. After the optimization studies for the derivatization and microextraction parameters, limit of detection (LOD) and limit of quantitation (LOQ) for the developed SADF-LPME method were found to be 48.0 and 159.9 mu g/kg, respectively. Recovery studies were implemented to verify the applicability and accuracy of the developed method for human urine and serum samples. The SADF-LPME method gave low percent recovery results (30.5-61.0%) for the spiked urine and serum samples showing that it failed to minimize or eliminate matrix effects for the analyte. Hence, methamphetamine acetamide-d3 was synthesized and purified in our research laboratory to be used as meth amphetamine isotopic analogue in the ID4 method. When the SADF-LPME method was combined with ID4, the percent recovery values for urine and serum samples were calculated as 99.7-100.0% and 99.4-100.2%, respectively. These results demonstrated the applicability and accuracy of the proposed method for urine and serum samples.
Keywords: Methamphetamine; Isotope dilution; Gas chromatography mass spectrometry; Derivatization; Spray assisted droplet formation-liquid phase; microextraction; AMPHETAMINE-TYPE STIMULANTS; ELEMENTAL SPECIATION; BIOLOGICAL SAMPLES; DRUGS; Pharmacology & Pharmacy; Toxicology